What's math got to do with it? : helping children learn to love their most hated subject--and why it's important for America - Boaler, Jo, 1964- (New York : Viking, 2008)
An alarming look at what's wrong with math education in the United States, and what we can do to change it The United States is rapidly falling behind the rest of the developed world in terms of math education, and the future of our economy depends on the quality of teaching that our children receive today. A recent assessment of mathematics performance around the world ranked the U.S. twenty-eighth out of forty countries in the study. When the level of spending on education was taken into account, we sank to the very bottom of the list. According to Jo Boaler, a professor of mathematics education at Stanford University, statistics like these are all too common?e have reached the point of crisis, and a new course of action is crucial. In this straightforward and inspiring book, Boaler outlines the nature of the math crisis by following the progress of students in middle and high schools over a number of years, observing which teaching methods are exciting students and getting results. Based on her research, she presents concrete solutions that will help reverse the trend, including classroom approaches, essential strategies for students, advice for parents on how to help children enjoy mathematics, and ways to work with teachers in schools. What's Math Got To Do With It? is an indispensable book for all parents and educators and anyone concerned about the mathematical and scientific future of our society
Introduction. Understanding the urgency -- 1. What is math? And why do we all need it? -- 2. What's going wrong in classrooms? Identifying the problems -- 3. A vision for a better future: effective classroom approaches -- 4. Taming the monster: new forms of testing that encourage learning -- 5. Stuck in the slow lane: how American grouping systems perpetuate low achievement -- 6. Paying the price for sugar and spice: how girls and women are kept out of math and science -- 7. Key strategies and ways of working -- 8. Giving children the best mathematical start: activities and advice -- 9. Making a difference through work with schools
Includes bibliographical references (pages 241-261) and index
Keywords: Mathematics -- Study and teaching; Teaching; Teaching